Clinical practice of mininally invasive gynaecological surgeries - Bhandari, Binaya Raj; Shrestha, Ranjana; Pradhan, Binita (Journal of Society of Surgeons of Nepal, 2018)
Introduction: Endoscopic gynaecological surgery which is a routine practice in outer world since last 40 years, is still at earlier phase in Nepal. This study was done to know the clinical practice of minimally invasive gynaecological surgeries in Minimally Invasive Diagnostic and Therapeutic (MIDAT) hospital. Methods: A hospital based descriptive study was conducted in gynaecological department of MIDAT hospital over 16 months period from 1st Bhadra 2071 to 30th Poush 2072 (17th August 2014 to 14th January 2016) among 115 women who underwent minimally invasive gynaecological surgeries (MIGS). Patient demographics, types of surgeries, indications of laparoscopy and hysteroscopy, reason for laparoscopic conversion, complications of surgeries and hospital stay were analyzed. Results: There were total 115 minimally invasive gynaecological surgeries done in MIDAT hospital during study period. Laparoscopic gynaecological surgeries and hysteroscopy were performed in 86 (75%) and in 29 (25%) women respectively. Among laparoscopy, laparoscopic hysterectomy 31 (36%) was the more common operation. During laparoscopy, conversion to open was done in nine (10.5%) patients. Complications of MIGS were seen in three (3.5%) women. Conclusions: MIGS has acceptable morbidity, smooth post operative recovery and shorter hospital stay. In recent time, MIGS is gradually becoming popular in Nepal.